PENGARUH PROFITABILITY, LEVERAGE, FIRM SIZE, DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDING - Santi, Santi; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence about the effect of profitability, leverage, firm size and growth opportunity on cash holding in manufacturing companies listed in Indonesia Stock Exchange (IDX) in the period of 2018-2020. This research used 74 manufacturing companies that have been selected by using purposive sampling technique. The data used in this study were processed using SPSS program and Microsoft Excel. The results indicate that profitability has positive significant effect on cash holding and leverage has negative significant effect on cash holding. Firm size and growth opportunity have no significant effect on cash holding.